A constructivist framework for disaster risk policy in Zimbabwe. (19th April 2021) - Chipangura, Paul; Niekerk, Dewald Van; Waldt, Gerrit Van Der
While the academic literature has established the importance of the constructivism perspective in disaster risk management, there remains a gap in how to embrace constructivism in disaster risk decision making in many countries. The framework presented in this article is a step towards translating the conceptualisation of disaster risk as a social construct into a practical set of arrangements that practitioners can use to navigate the complex and fluid landscape of disaster risk problems and solutions, especially in Zimbabwe. The framework constitutes a five-stage process of inclusivity, diagnostic, prognostic, and motivational framing and evaluation. The article concludes that this framework could help in increasing stakeholder empowerment thereby making planning and decision-making process more transparent and democratic. Furthermore, this framework may facilitate the building of trust, ownership, and consensus that ultimately increase the legitimacy to policy decisions and stakeholder support in disaster risk reduction.